The slip-ups of corporate governance in Botswana Public Enterprises - Motshegwa, B.; Mooketsane, K.; Bodilenyane, K. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
Public enterprises play a vital role in economic development, yet they suffer from various problems. Mismanagement, corruption, personal and political interest masquerade the role played by these state enterprises. Several cases of mismanagement and corruption have been reported in most public enterprises in Botswana. This paper uses a documentary analysis to unearth some of the problems and challenges faced by public enterprises in Botswana, in particular the paper uses Botswana development Corporation and Botswana Railways as case studies. Corporate slip-ups continue to plague Botswana despite the adoption of the King Code of Governance. Corporate governance gaffes have happened in big public corporations like Botswana Development Corporation where government ended up being the biggest looser when the glass company plant materials were auctioned for a pittance. Other public enterprises such as Botswana Meat Commission, Botswana Railways, Air Botswana, have also been hard hit by bad governance. The paper uses literature on best practices of governance to interrogate how corporate governance is practiced in the public sector. Boards of directors are mandated to ensure proper governance based on principles of corporate governance. They should safeguard that decision making process is independent of government, injecting values of transparency and accountability, and guarantee shareholder (citizens) trust. If indeed a good system of corporate governance is executed, public enterprises can graduate from relying on government subsidies, and come to be profitable entities. However, a challenge remains in running public enterprises like businesses where tax payers and owners of means of production are treated as customers and spectators. Another challenge that remains before Public Enterprises Evaluation and Privatisation Agency (PEEPA) is to reposition itself so that public enterprises become relevant entities manned by Board of directors who are accountable.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Corporate governance; Botswana Development Corporation; Botswana railways; Public enterprises; Board of directors; Stakeholders; Corporate governance -- Botswana; Government business enterprises -- Botswana; Government accountability